Media, civilization and the international order. (May 2020) - Athique, Adrian
This article is intended to provoke debate around the assumed relationships between media, culture and civilization. To begin with, it considers how the concept of civilization has been framed, and periodically re-framed, in media theory by shifts in the international order of communication. In parallel with this historiography, the article revisits a body of research that explored the evolution of television audiences in alignment with the cultural geography of the world. Taking account of this transition from national media institutions to supra-national markets, and the apparent dissolution of the worldwide web into geolinguistic networks more recently, this article argues that media systems and audiences are subject to the primacy of civilizational mass in the world system. Consequently, this article draws attention to persistent anxieties around a purported crisis of civilization, and the political imperatives for cultural studies scholarship to engage with both the concept and scale of civilization.